(untitled) (Applied Biological Research, 2025)
The health and nutritional profiles of autistic children are significantly influenced by abnormal food behaviors, compounded by mal-digestion and malabsorption. This study aimed to assess the nutritional status, food behavior, and the impact of atypical behaviors and dietary restrictions on the nutritional well-being of autistic children identified according to DSM-IV criteria.A total of 60 autistic children, both boys and girls aged 5–16 years, were evaluated. The findings revealed that 70% of the children were shorter and 65% were lighter than the NCHS (National Center for Health Statistics) standards. Most children exhibited normal hemoglobin levels, and immunoglobulin G (IgG) and immunoglobulin A (IgA) levels were generally within normal ranges. However, immunoglobulin E (IgE) levels were significantly elevated in all children.Food selectivity, reduced appetite, and picky eating emerged as the predominant factors influencing their food habits. These classical food behaviors were shown to impair the nutritional status and overall well-being of autistic children.